Mr. Science and Chairman Mao's Cultural Revolution : Science and Technology in Modern China - Brock, Darryl E.; Cao, Cong; Cheng, Yinghong; Greenhalgh, Susan; Han, Dongping; Mikita, Michael A.; Schmalzer, Sigrid; Solomone, Stacey; Volti, Rudi; Wei, Chunjuan Nancy; Xu, Yibao (Lexington Books, 2012)
Despite the verdict of the Cultural Revolution as a disaster for China, a number of scholars have called for re-examining socialist science under Mao's aegis. Western observers once found much to admire in Chairman Mao's mass science, with its origins in the May Fourth era. This collection represents diverse viewpoints on social and scientific enterprises of that era, probing medicine, the space program and even the one-child policy as direct outcomes of earlier Maoist science.